EVALUATION Of QUALITY CONTROL FOR THE END OF PRODUCT IN “UD NANANG” BRICK COMPANY YOGYAKARTA - Dona, Evi; Lastari, SE.,MM, Siwi (Management, 2010)
The purpose of this study was to determine whether the product is damaged in "UD Nanang" brick company Yogyakarta is still within the control limits and whether the factors that cause damage to the company´s products brick of "UD Nanang" Yogyakarta. Data collection using observation and interviews. Data analysis technique used is the control chart for attributes or "P-Chart" by calculating the mean of the damage (P), compute the standard deviation (Sp) and determine the area of quality standards (UCL / Upper Control Limit / Border Control Top, and LCL / Lower Control Limit / Lower Control Limit). Results from analysis of data on quality control carried out by the company building block “UD Nanang”, that the implementation of quality control in the company building block “UD Nanang” still bad, so that the resulting product quality can not meet the standards set by the company, namely of 4:50%. Although the difference in the level of the average percentage of damage to bricks to the standards set by small companies, which in 2003 amounted to 0.5%, 0.32% in 2004 and in 2005 of 12:49%. The damage that occurs in the final product is also caused by a lack of rigor and discipline workers who handle the production process. Keywords: defective product, quality control, precision, discipline workers.